2014
DOI: 10.1063/1.4892984
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity scaling and electron relaxation times in metallic nanowires

Abstract: We study the resistivity scaling in nanometer-sized metallic wires due to surface roughness and grain-boundaries, currently the main cause of electron scattering in nanoscaled interconnects. The resistivity has been obtained with the Boltzmann transport equation, adopting the relaxation time approximation (RTA) of the distribution function and the effective mass approximation for the conducting electrons. The relaxation times are calculated exactly, using Fermi's golden rule, resulting in a correct relaxation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…10 together with the approximated solution by putting the relaxation time ratio on the right-hand-side equal to 1, assuming equal lifetimes for the initial and final states. 16 The resistivity drop is only apparent in the self-consistent solution of the BTE because it is the only solution that solves the coupled system of equations, determining the scattering lifetimes correctly. Two data points of Fig.…”
Section: B Metallic Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…10 together with the approximated solution by putting the relaxation time ratio on the right-hand-side equal to 1, assuming equal lifetimes for the initial and final states. 16 The resistivity drop is only apparent in the self-consistent solution of the BTE because it is the only solution that solves the coupled system of equations, determining the scattering lifetimes correctly. Two data points of Fig.…”
Section: B Metallic Nanowiresmentioning
confidence: 99%
“…It was shown that the resistivity due to SR can have very different values and scaling behavior for different values of SR standard deviation and correlation length. 16 A disadvantage of the Prange-Nee approximation is that it takes the infinite barrier limit of an expansion for small roughness sizes, which often falls short to determine the wave function overlap, especially in the case of large roughness sizes, highly oscillating wave functions or low barrier heights. For metallic nanowires one should definitely be careful, as there are many subbands and, hence, high wave vector values in the confinement direction are generally present.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] This reverse effect of dimensional scaling became particularly apparent in the late 90's as the industry left the realm of the micron (i.e. micro-electronics) and entered into the realm of the nanometer (i.e.…”
mentioning
confidence: 99%
“…In this work we present an alternative approach, based on an analytic solution of the multi-subband Boltzmann transport equation (BTE) within the effective mass approximation for the conduction electrons. The relaxation times (RTs) are calculated self-consistently and Fermi's golden rule (FGR) is used to obtain the scattering rates [7]. The FGR matrix elements only rely on (statistical) physical parameters of the scattering mechanisms, such as the shape, density and energy barrier strength for GBs and the standard deviation and correlation length for SR.…”
Section: Introductionmentioning
confidence: 99%